Infrared spectra of some fructans. Issue 3 (2002) - Grube Grube, M. M.; Bekers Bekers, M. M.; Upite Upite, D. D.; Kaminska Kaminska, E. E.
Abstract : The FT–IR spectra of fructan – inulin (RAFTILINE), widely applied in the food industry and crystalline fructose as the main component of fructans, were studied. Special interest was to study the spectra of the levan precipitate and fructan syrup – produced by Zymomonas mobilis during the fermentation on sucrose–based medium. It was shown that levan precipitate and fructose syrup does not contain lipids and nucleic acids. Levan precipitate consists of ∼93% of fructose and admixture of glucose, mannan and enzyme – levansucrase. Fructan polymer inulin consists principally of linear chains of fructosyl units linked by a β (2–1) bonds ended by a glycosyl unit. The links between the molecules are of a very special type: the β (2–1) form (2) [8]. The bacterial fructans of the levan type are high molecular weight polymers, i.e., they are composed of β –(2, 6)–ructosyl–fructose linked molecules and side chains [17]. The FT–IR spectra of levan, apart from inulin's, in the carbohydrate region 900–1200 cm –1, shows overlapping broad band with maximum at ∼1030 cm –1 and stronger absorption at ∼940 cm –1 . The differences in both spectra could be caused by different structure and glucose, sucrose and mannan influence.